Optimizing sowing patterns in winter wheat can reduce N2O emissions and improve grain yield and NUE by enhancing N uptake - Zhang, Xiu; Liu, Manyu; Zheng, Feina; Dong, Yuanjie; Hua, Yifan; Chu, Jinpeng; He, Mingrong; Dai, Xinglong (Frontiers in Plant Science, 2023)
Increasing nitrogen (N) input is essential to satisfy the rising global wheat demand, but this increases nitrous oxide (N2O) emissions, thereby exacerbating global climate change. Higher yields accompanied by reduced N2O emissions are essential to synergistically reduce greenhouse warming and ensure global food security. In this study, we conducted a trial using two sowing patterns (conventional drilling sowing [CD] and wide belt sowing [WB], with seedling belt widths of 2–3 and 8–10 cm, respectively) with four N rates (0, 168, 240, and 312 kg ha-1, hereafter N0, N168, N240, and N312, respectively) during the 2019–2020 and 2020–2021 growing seasons. We investigated the impacts of growing season, sowing pattern, and N rate on N2O emissions, N2O emissions factors (EFs), global warming potential (GWP), yield-scaled N2O emissions, grain yield, N use efficiency (NUE), plant N uptake and soil inorganic N concentrations at jointing, anthesis, and maturity. The results showed that sowing pattern and N rate interactions influenced the N2O emissions markedly. Compared to CD, WB significantly reduced cumulative N2O emissions, N2O EFs, GWP, and yield-scaled N2O emissions for N168, N240, and N312, with the largest reduction seen at N312. Furthermore, WB markedly improved plant N uptake and reduced soil inorganic N compared to CD at each N rate. Correlation analyses indicated that WB mitigated the N2O emissions at various N rates mainly through efficient N uptake and reduced soil inorganic N. The highest grain yield occurred under a combination of WB and N312, under which the yield-scaled N2O emissions were equal to the local management (sowing with CD at N240). In conclusion, WB sowing could synergistically decrease N2O emissions and obtain high grain yields and NUEs, especially at higher N rates.